Assessment of Leaders’ Adherence to Public Leadership Code of Ethics in Promoting Good Governance in the Local Government Authorities: Case Study of Kinondoni Municipality – Dar es Salaam, Tanzania (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The Public Leadership Code of Ethics Act No. 13 of 1995 was established in Tanzania's public sector, including local government authorities (LGAs), to promote ethical conduct among public leaders. However, leadership scandals, such as corruption and fraud, remain frequently reported in media, literature, and government reports concerning LGAs. This study sought to assess leaders' adherence to the public leadership code of ethics in promoting good governance within the Kinondoni Municipality. The study was guided by an interpretivist epistemology and employed a qualitative design. A total of 85 participants, including leaders and ordinary citizens, were selected using convenience and purposive sampling techniques. Data were collected through interviews, focus group discussions, and document reviews, and were analyzed using thematic analysis. The findings indicate that adherence to the code of ethics among local government leaders was low, as many were found to be unethical and pursued personal interests. The study recommends that the government collaborate with relevant stakeholders to implement necessary reforms. Furthermore, ethics education should be integrated from the family level through university education to address the inadequacy of social and administrative ethics.